A portrait of the artist as a young man - McKenna, T. P., 1929-2011; Gielgud, John, 1904-2000; Hogan, Bosco; Joyce, James, 1882-1941; Strick, Joseph (Films Incorporated, 1983)
Presents the childhood, adolescence, and early manhood of an Irish poet-scholar.